Identification of goldfish (Carassius auratus L.) leukocyte immune-type receptors shows alternative splicing as a potential mechanism for receptor diversification. (September 2020) - Wang, Jiahui; Belosevic, Miodrag; Stafford, James L.
Highlights: Genomic and expression analysis of goldfish LITR-types demonstrates their dynamic immunoregulatory potentials. Goldfish LITRs may be further diversified during immune cell responses. Goldfish myeloid cells co-express LITR-types with variable functional potentials. Fish LITR-types likely participate in innate cellular defence mechanisms. Abstract: Leukocyte immune-type receptors (LITRs) are a multigene family of teleost immunoregulatory proteins that share structural, phylogenetic, and likely functional relationships with several innate immune receptor proteins in other vertebrates, including mammals. Originally discovered in channel catfish ( Ictalurus punctatus ), representative IpLITR-types have been shown to regulate diverse innate immune cell effector responses including phagocytosis, degranulation, and cytokine secretion. To date, IpLITRs have been primarily characterized using mammalian cell line expression systems, therefore many unanswered questions remain regarding their actual regulatory roles in fish immunity. In the present study, we report on the preliminary molecular characterization of five goldfish ( Carassius auratus ) CaLITR-types and the identification of several putative splice variants of these receptors cloned from various goldfish tissues and primary myeloid cell cultures. In general, CaLITR mRNA transcripts were detected in all goldfish tissues tested, and also in primary kidney macrophage and neutrophil cultures. Specifically, CaLITR1 is a functionally ambiguous receptor with no charged amino acids in its transmembrane (TM) segment and is devoid of tyrosine-based signaling motifs in its short cytoplasmic tail (CYT) region. CaLITR2 is a putative activating receptor-type that contains immunotyrosine-based activation motifs (ITAMs) within its long CYT region, and CaLITR3 has a positively charged TM segment, suggesting that it may recruit intracellular stimulatory adaptor signaling molecules. CaLITR4 and CaLITR5 appear to have diverse signaling capabilities since they contain various immunoregulatory signaling motifs within their CYT regions including putative Nck and STAT recruitment motifs as well as ITAM-like and ITIM sequences. We also identified putative CaLITR splice variants with altered extracellular Ig-like domain compositions and variable CYT regions. Interestingly, this suggests that alternative splicing-mediated diversification of CaLITRs can generate receptor forms with possible variable binding and/or intracellular signaling abilities. Overall, these findings reveal new information about the teleost LITRs and sets the stage for exploring how alternative splicing leads to the functional diversification of this complex multigene immunoregulatory receptor family.